2017
DOI: 10.4025/psicolestud.v22i1.32518
|View full text |Cite
|
Sign up to set email alerts
|

Interações Entre Memória Operacional E Criatividade: Revisão Sistemática

Abstract: RESUMO.A criatividade e a memória operacional são marcadores de sucesso acadêmico e profissional. Paradoxalmente, estudos correlacionais nem sempre encontram associações entre esses constructos, algumas pesquisas evidenciam associações positivas entre os mesmos, e outras, associações negativas. Provavelmente, os achados contraditórios decorrem de parâmetros distintos, sendo importante identificá-los para uma compreensão mais coerente de tais relações. Assim, esta revisão sistemática de literatura teve como obj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Once n-back tasks and complex span tasks apparently evaluate different processes (Ribeiro et al, submitted; Kane et al, 2007), WM researches should consider the differences between tasks and how they affect the result explanations (Redick and Lindsey, 2013; Remoli and Santos, 2017). That seems to be crucial for explaining the outcomes and for the replication of future studies (Ribeiro et al, submitted).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Once n-back tasks and complex span tasks apparently evaluate different processes (Ribeiro et al, submitted; Kane et al, 2007), WM researches should consider the differences between tasks and how they affect the result explanations (Redick and Lindsey, 2013; Remoli and Santos, 2017). That seems to be crucial for explaining the outcomes and for the replication of future studies (Ribeiro et al, submitted).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, complex span tasks and n-back tasks are the most used WM measures (Miyake and Shah, 1999), since both require storing and maintain the information of a set of stimuli, and inhibiting interference of the signals recently presented (St Clair-Thompson and Gathercole, 2006). But there are dissimilarities, complex span tasks request keeping a serial order in mind at the same time of an ongoing cognitive task (Daneman and Merikle, 1996; Unsworth and Engle, 2007; Conway and Kovacs, 2013), while n-back tasks demand a constant updating of the relevant information (Kane et al, 2008; Wilhelm et al, 2013; Remoli and Santos, 2017). Apart from that, there are low correlations between n-back tasks and complex span tasks leading a conclusion that both evaluate different processes of WM (Kane et al, 2008; Redick and Lindsey, 2013), particularly concerning to the influence of emotional states (Ribeiro et al, submitted).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that traffic noise causes physical and mental effects such as mental stress [6][7][8][9][10][11], memory [10][11][12], anxiety [13][14][15], insomnia [16][17][18][19][20][21], traffic noise-related diseases [20][21][22][23], and physical and mental health problems. Although these studies differed from the present study, they are closely related as these physical and mental effects can affect innovation [24][25][26][27]. On this basis, this study statistically linked the two impacts provided evidence for the impact of traffic noise on innovation and provided a feasible scheme for health management to solve the problems associated with traffic noise.…”
Section: Discussionmentioning
confidence: 64%
“…Traffic noise pollution has become a significant public hazard in urban areas, causing physical and psychological harm to residents, and has been shown to cause mental stress [6][7][8][9], memory decline [10][11][12], anxiety [13][14][15], insomnia [16][17][18][19], and traffic noise-related diseases [20][21][22][23]. These harmful effects of traffic noise can impact the quality of life, learning efficiency, and work innovation [24][25][26][27]. Previous studies have mainly focused on the effects of traffic noise on health, with few studies exploring the impact of traffic noise on innovation.…”
Section: Introductionmentioning
confidence: 99%
“…Creativity is the cognitive ability to generate solutions that are both original and useful (Paulus & Nijstad, 2003), and it plays a vital role in any field to secure innovation and progress (Adaman & Blaney, 1995; Kim, 2011; Newton & Newton, 2010; Remoli & Santos, 2017; Ritter & Mostert, 2017). Divergent thinking is the process of coming up with different solutions for a problem (Guilford, 1967).…”
mentioning
confidence: 99%